Forest-Grown Coffee for Village Prosperity: A Business Model Analysis - Sebayang, Asnita; Nurfahmiyati, Nurfahmiyati; Haviz, Meidy (International Journal of Entrepreneurship and Sustainability Studies, 2025)
The leading commodity of forest coffee is a strategic opportunity for the local economy's strength. This study uses a Participatory Action Research (PAR) approach that combines a qualitative approach with participatory action as part of an effort to increase the role of coffee as the competitive advantage of Mekarmanik Village in Bandung Regency. Identifying the business model using the Hijrah Tool Business Model approach indicates that this business has a promising business model. The main sources of strength of the coffee business are the geographical aspects that impact the quality of coffee with unique flavors, social capital, strategic partnerships through the role of cooperatives, and skilled human resources. The limitation of coffee commodity development as the village's leading commodity is related to area development, which is mostly in protected forest areas, a lack of accessibility, particularly connectivity (infrastructure), a lack of product marketing, high dependency on middlemen, and managerial obstacles. This study recommends a triple-helix approach that involves coffee farmers/businesses in the village, the government, and universities to increase community income more sustainably and equitably.